Switch to Autophagy the Key Mechanism for Trabecular Meshwork Death in Severe Glaucoma - Rao A (Dove Medical Press, 2021)
Aparna Rao,1,2 Prity Sahay,1,2 Munmun Chakraborty,1,2 Birendra Kumar Prusty,3 Sandhya Srinivasan,4 Gagan deep Jhingan,4 Pragyan Mishra Snr,2 Rahul Modak,2 Mrutyunjay Suar2 1Glaucoma Service, MTC campus, L.V. Prasad Eye Institute, Bhubaneswar, Odisha, 751024, India; 2KIIT School of Biotechnology, Bhubaneswar, Odisha, India; 3Institute of Life Sciences, Bhubaneswar, Odisha, India; 4Vproteomics, Green Park, New Delhi, IndiaCorrespondence: Aparna Rao Email vinodini10375@yahoo.comPurpose: The key differences in cell death mechanisms in the trabecular meshwork (TM) in adult moderate and severe primary glaucoma remain still unanswered. This study explored key differences in cell death mechanisms in the trabecular meshwork (TM) in adult moderate and severe primary glaucoma.Design: In-vitro laboratory study on surgical specimens and primary cell lines.Methods: Select cell death-related proteins differentially expressed on mass spectrometric analysis in ex-vivo dissected TM specimens patients with severe adult primary open-angle (POAG) or angle-closure glaucoma (PACG) compared to controls (cadaver donor cornea) were validated for temporal changes in cell death-related gene expression on in-vitro primary human TM cell culture after 48 hours (moderate) or 72 hours (severe) oxidative stress with H2O2 (400– 1000 uM concentration). These were compared with histone modifications after oxidative stress in human TM (HTM) culture and peripheral blood of patients with moderate and severe glaucoma.Results: Autophagy-related proteins seemed to be the predominant cell-death mechanism over apoptosis in ex-vivo dissected TM specimens in severe glaucoma. Analyzing HTM cell gene expression at 48 hours and 72 hours of oxidative stress, autophagy genes were up-regulated at 48– 72 hours of exposure in contrast to apoptosis-related genes, showing down-regulation at 72 hours. There was associated increased expression of H3K14ac in HTM after 72 hours of oxidative stress and in peripheral blood of severe POAG and PACG.Conclusion: A preference of autophagy over apoptosis may underlie stage transition from moderate to severe glaucoma in the trabecular meshwork or peripheral blood, which may be tightly regulated by epigenetic modulators.Keywords: trabecular meshwork, cell death, autophagy, apoptosis, glaucoma